Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Prove the Identity: tan^2 x + 6 tanx + 5 / sec^2 x - 2 = tanx + 5 / tanx - 1?
2 Answers
- 4 years ago
Hint: sec(x)^2 - tan(x)^2 = 1
tan(x)^2 + 6 * tan(x) + 5 =>
(tan(x) + 5) * (tan(x) + 1)
sec(x)^2 - 2 =>
1 + tan(x)^2 - 2 =>
tan(x)^2 - 1 =>
(tan(x) - 1) * (tan(x) + 1)
You should be able to finish this.
- az_lenderLv 74 years ago
Maybe you mean
[tan^2(x) + 6 tan(x) + 5] / [sec^2(x) - 2]
= [tan(x) + 5] / [tan(x) - 1].
When you replace a horizontal fraction bar with a diagonal slash, symbols of inclusion (parentheses or brackets) are absolutely REQUIRED.
Anyway, since
tan^2(x) + 6 tan(x) + 5
= [tan(x) + 5] * [tan(x) + 1],
your equality reduces to
[tan(x) + 1] / [sec^2(x) - 2] = 1/[tan(x) - 1], or
[tan^2(x) - 1] = [sec^2(x) - 2],
but this is obvious because
tan^2(x) = sec^2(x) - 1.